Anesthetic Management of a Single Ventricle in Pediatric Patient Undergoing Open Duodeno–Duodenostomy Surgery: A Case Report - Lesmana, Pita Mora; I Putu Kurniyanta; Tjokorda Gde Agung Senapathi (HM Publisher, 2024)
Background: Duodenal atresia is a rare congenital disorder characterized by blockage of the small intestine. Open duodeno-duodenostomy is the surgery of choice to correct this condition. Case presentation: We report the case of a three-day-old baby girl with duodenal atresia and a functional single ventricle who underwent open duodeno-duodenostomy. The patient was born via caesarean section due to indications for a previous caesarean section in the mother and congenital abnormalities in the fetus. At birth, the patient showed signs of intestinal obstruction and cyanosis. Preoperative physical and laboratory examinations confirmed duodenal atresia and cardiac abnormalities. The patient underwent an open duodeno-duodenostomy without complications. The patent ductus arteriosus must be kept open to maintain systemic perfusion by maintaining PaO2 at 40 to 45 mmHg and SaO2 at 70% to 80%, along with the administration of prostaglandin agents. Good perioperative management and improvements in surgical procedures will increase the life expectancy of patients with single ventricle problems, especially hypoplastic left heart syndrome. The use of low-dose fentanyl induction agent, 1 MAC sevoflurane, and atracurium has been proven to produce favorable outcomes in these patients. Conclusion: Open duodeno-duodenostomy is a safe and effective operation for duodenal atresia. The patient in this case recovered well after surgery. Open duodeno-duodenostomy should be considered as the primary treatment option for duodenal atresia.